How to write a usuable user manual - Weiss, Edmond (Philadelphia: ISI Press, 1985)
Contents: part. 1 toward a science of user documentacion. part. 2. a structure approach to user documentacion. part. 3. the future of user documentacion 4. appendixes
Keywords: Computers Handbook Manuals